EVALUASI PEMBELAJARAN MENGGUNAKAN MODEL CIPP BERBASIS COLLABORATIVE PROJECT BASED LEARNING - Afnia Dwi Febriani Afnia; Arief Rahman Yusuf Arief; Sigit Dwi Laksana Sigit (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The implementation of Collaborative Project-Based Learning (CPjBL) in vocational education needs to be evaluated to ensure alignment between instructional planning, implementation, and learning outcomes in supporting students' competency achievement. This study aims to evaluate the implementation of Collaborative Project-Based Learning (CPjBL) in the Audio Video Engineering Program at SMKS Brawijaya Ponorogo using the Context, Input, Process, Product (CIPP) evaluation model. The study employed a qualitative descriptive approach involving the principal, the vice principal for curriculum affairs, and vocational teachers as research participants. Data were collected through observations, interviews, and document analysis, and were analyzed using the Miles and Huberman interactive analysis model. The findings indicate that, in terms of the context aspect, the implementation of CPjBL is aligned with the Merdeka Curriculum through project-based learning that integrates technical competencies, collaboration, and problem-solving skills in accordance with workplace demands. Regarding the input aspect, the school is supported by teachers' competencies in designing and facilitating project-based learning, the availability of laboratories and practical equipment, and strong school management support through the provision of facilities, policies, and instructional supervision. In the process aspect, learning is carried out through the stages of project planning, collaborative work, monitoring, reflection, and evaluation, thereby encouraging students' active participation in project completion. In the product aspect, CPjBL enhances students' critical thinking, collaboration, communication, and technical skills, as demonstrated by their successful production of fully functional active speakers and Capacitor Discharge Ignition (CDI) systems that meet the competency standards of the Audio Video Engineering Program. In conclusion, CPjBL has proven to be an effective instructional model and is worthy of further development as a vocational learning approach to strengthen 21st-century competencies and improve students' work readiness. ABSTRAK Implementasi Collaborative Project Based Learning (CPjBL) pada pendidikan kejuruan perlu dievaluasi untuk memastikan kesesuaian antara perencanaan, pelaksanaan, dan hasil pembelajaran dalam mendukung pencapaian kompetensi peserta didik. Penelitian ini bertujuan untuk mengevaluasi implementasi Collaborative Project Based Learning (CPjBL) pada Program Keahlian Teknik Audio Video di SMKS Brawijaya Ponorogo menggunakan model evaluasi Context, Input, Process, Product (CIPP). Penelitian menggunakan pendekatan deskriptif kualitatif dengan subjek Wakil Wakil Kepala Sekolah Bidang Kurikulum Bidang Kurikulum, wakil Wakil Wakil Kepala Sekolah Bidang Kurikulum Bidang Kurikulum bidang kurikulum, dan guru produktif. Data dikumpulkan melalui observasi, wawancara, dan studi dokumentasi, kemudian dianalisis menggunakan model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa pada aspek context, implementasi CPjBL selaras dengan Kurikulum Merdeka melalui pembelajaran berbasis proyek yang mengintegrasikan kompetensi teknis, kolaborasi, dan pemecahan masalah sesuai kebutuhan dunia kerja. Pada aspek input, sekolah didukung oleh kompetensi guru dalam merancang dan memfasilitasi pembelajaran berbasis proyek, ketersediaan laboratorium serta peralatan praktik, dan dukungan manajemen sekolah melalui penyediaan sarana, kebijakan, serta supervisi pembelajaran. Pada aspek process, pembelajaran dilaksanakan melalui tahapan perencanaan proyek, kerja kolaboratif, monitoring, refleksi, dan evaluasi sehingga mendorong partisipasi aktif peserta didik dalam penyelesaian proyek. Pada aspek product, CPjBL meningkatkan kemampuan berpikir kritis, kolaborasi, komunikasi, dan keterampilan teknis peserta didik yang ditunjukkan melalui keberhasilan menghasilkan produk speaker active dan Capacitor Discharge Ignition (CDI) yang berfungsi dengan baik serta sesuai dengan kompetensi Program Keahlian Teknik Audio Video. Dengan demikian, CPjBL terbukti efektif dan layak dikembangkan sebagai model pembelajaran vokasi untuk mendukung penguatan kompetensi abad ke-21 dan kesiapan kerja peserta didik.